Provisions of Parliamentary Investigation and its Effects in the Iraqi Constitution of 2005 - Omar, Shoresh Hassan; Rahman, Shalaw Sabah Abdul (Journal of Legal and Political Studies, 2016)
The parliamentary investigation is an effective censorship means for the legislative authority on the acts of the executive authority, so that the legislative authority through this mean it can reach the knowledge of the facts, and that through this right it can form investigative committees to do the necessary investigations on any subject within their competence and make the appropriate decision on the issue proposed to investigate, and given the importance of this means provides the majority of the constitutions on this right to the legislative authority, the Iraqi constitution Permanent were omitted to provide on this right for the Iraqi Council of Representatives, and has been stipulated in the rules of procedure of the Council of Representatives and through the text that the Council has the right to form committees to detect investigative facts in issues under investigation within the council of Representatives. Despite the omission of the Iraqi constitution to provide this right, also the rules which included the procedure of the council of Representatives streaked by a lot of deficiencies and ambiguities as well, and through this study we have gave several observations and suggestions for addressing those gaps and deficiencies in the future.
Keywords: parliamentary investigation; executive authority; Legislative; Iraqi constitution